MARKETING STRATEGY ANALYSIS TO INCREASE SALES OF DELIVERY SERVICES AT GERAI MULTIEKSPRES - Susanto, Denies; Fuadi, Fuadi; Novitasari, Sela (Yayasan Education and Social Center, 2025)
This study aims to formulate an appropriate strategy to increase sales for Gerai Multiekspres, a delivery service company in Indonesia. This research employed a qualitative case study method. Data were collected through document review, interviews, and observations. The analysis was conducted using several strategic management tools, including the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), Strategic Position and Action Evaluation (SPACE) matrix, and Internal-External (IE) matrix. The IFAS and EFAS calculations showed a score of 2.83 for strengths, 0.33 for weaknesses, 2.25 for opportunities, and 0.70 for threats. The SPACE matrix analysis indicated that Gerai Multiekspres is in quadrant I with a positive SW (Strengths, Weaknesses) value of 2.50 and a positive OT (Opportunities, Threats) value of 1.55. Furthermore, the IE matrix analysis showed that Gerai Multiekspres is in Cell I with a total weighted score of 3.15 for IFAS and 2.95 for EFAS. The findings suggest that Gerai Multiekspres should pursue an aggressive growth strategy, given its dominance of strengths and opportunities, as well as a favorable position in the SPACE and IE matrices